Etiología y prevalencia de las abrasiones dentales en pacientes adultos de la Clínica Odontológica N° 1 de la Carrera de Odontología de la Universidad Nacional de Loja - Tandazo López, Geovanna Lizbeth (2019)
Dental abrasion is the wear of the tooth structure that generates the loss of hard tissues at the level of the amelocementary limit. It is important to make an early diagnosis and identify your etiology to carry out an appropriate treatment. The research was observational, descriptive and prospective, the objective of this research work was determine the etiology and prevalence of dental abrasions in patients aged between 18 and 60 years, who attend to Clinic N°1 of the Dentistry Career of the National University of Loja. The study sample was of 96 patients, in whom an evaluation was carried out that included: clinical exploration, recorded in the observation guide and the application of a survey to discover the possible etiological factors that influence the appearance of abrasion. The results showed a prevalence of abrasion in 13,5%, the sex most affected was female sex (76,9%), the most affected age range was 40 to 64 years (69,2% ); The most affected dental group was the premolar group, mainly dental piece # 24 (30,7%) and the degree of severity that was most prevalent according to the Smith and Knight Index was Grade 1 (62%). Among the most predisposing etiological factors we have: brushing teeth more than 2 times a day (OR = 1.56), the use of soft bristle brush (OR = 1.48), the habit of clean your teeth with toothpicks (OR = 1.53) and the habit of cutting thread or tape with your teeth (OR = 1.08). The above concludes that the prevalence of dental abrasion is low in patients who attend the dental clinic and is related to daily brushing times, the type of toothbrush bristles and parafunctional habits. Key words: tooth wear, tooth abrasion, Smith & Knight index, etiological factors, parafunctional habits.